Sosialisasi Pembuatan dan Pemasangan Tanda Batas Tanah di Dusun Simbaringin Desa Sidosari Kecamatan Natar Kabupaten Lampung Selatan - FX Sumarja; Upik Hamidah; Ati Yuniati (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2017)
Abstract — Problems activities: 1) How to improve understanding of the rights and obligations of landowners in the hamlet Simbaringin, Sidosari Village, District Natar, South Lampung regency,?; 2) How to improve the skills of the owner of the land in the manufacture and installation of boundary marks? Problem solving is done by communicating the law on the rights and obligations of land owners, especially concerning land boundary markers and installation process. Solution methods: lectures, discussions and demonstrations. The evaluation results increased knowledge and understanding, before the activities of the mean value of 55.25, and after the activities of the mean value of 73.75. Aspects of attitude before the event no one can prepare for the installation of boundary marks, after the intervention there were 22 (55%) of people who can. The results of the activities that: there is an increased ability knowledge and understanding of the law, and be able to change the attitude from which you can not, be able to prepare. Suggested activity is continued, so that increased knowledge and understanding of the land law, to reduce land disputes. Keywords — demonstration, dissemination, land boundary markers